Transparency in Agriculture and Natural Resources: Defining Transparent Communication - Joy N. Rumble (EDIS, 2015)
When we think about transparency, we usually think about business, public relations, and government; however; transparency is also an important consideration in agriculture and food industries. Defined as openness and the opposite of secrecy, transparency can be conceptualized as a communication strategy that the agricultural industry can use to interact with consumers and other audiences. This 3-page fact sheet defines transparent communication as containing substantial information, incorporating audience participation, and maintaining accountability. Written by Joy N. Rumble, and published by the UF Department of Agricultural Education and Communication, August 2015.